The Influence of Continuous Exercising on Chronotropic Incompetence in Multi-Episode Schizophrenia - Herbsleb, Marco; Keller-Varady, Katriona; Wobrock, Thomas; Hasan, Alkomiet; Schmitt, Andrea; Falkai, Peter; Gabriel, Holger Horst Werner; Bär, Karl-Jürgen; Malchow, Berend (Frontiers in Psychiatry, 2019)
People with schizophrenia die on average 15-20 years earlier than age and gender matched controls in the general population. An essential part of this excess mortality in people with schizophrenia is caused by physical illnesses. Among the physical illnesses, cardiovascular disease (CVD) has been identified as the most common natural cause of death in up to 40-45% of the cases. Chronotropic incompetence (CI), the inability of the heart to increase its beating frequency in proportion to increased physical activity, is an established independent cardiovascular risk factor. It was recently described in patients with schizophrenia and might help explain the reduced physical fitness in these patients and the inability of a subgroup of patients to benefit from exercise interventions. In this study, we tried to replicate the occurrence of CI in an independent sample of patients with schizophrenia and evaluated whether CI can be influenced by a continuous endurance training of 12 weeks. Therefore, we re-analyzed the fitness testing data of 43 patients with schizophrenia and 22 aged and gender matched healthy controls. Parameters of aerobic fitness and chronotropic response to exercise were calculated. Patients with schizophrenia were less physically fit than the healthy controls and displayed a significantly higher heart rate at rest. 10 of 43 patients with schizophrenia and no healthy control subject were classified as chronotropically incompetent. Chronotropic response to exercise did not change significantly after twelve weeks of continuous aerobic exercise training. No differences were observed for baseline heart rate and peak heart rate in both subgroups of schizophrenia patients. Aerobic fitness did not improve significantly in the patients with schizophrenia classified as chronotropically incompetent. Our results confirm the occurrence of CI in patients with multi-episode schizophrenia. This should be taken into account when planning an exercise or lifestyle intervention studies in this population. Schizophrenia patients with CI do not seem to benefit as well as schizophrenia patients without CI from aerobic exercise training interventions. Larger, prospective randomized controlled clinical trials with different training interventions are urgently needed to address the topic of schizophrenia patients not responding to exercise and the relationship to the illness itself.